Why sustainable population growth is a key to climate change and public health equity - Howat, Peter; Stoneham, Melissa (Australian Health Promotion Association, 2011)
Australia’s population could reach 42 million by 2050. This rapid population growth, if unabated, will have significant social, public health and environmental implications. On the one hand, it is a major driver of climate change and environmental degradation; on the other it is likely to be a major contributor to growing social and health issues including a decline in quality of life for many residents. Disadvantaged and vulnerable groups will be most affected. The environmental, social and health-related issues include: pressure on the limited arable land in Australia; increased volumes of industrial and domestic waste; inadequate essential services; traffic congestion; lack of affordable housing; declining mental health; increased obesity problems; and inadequate aged care services. Many of these factors are related to the aggravation of climate change and health inequities. It is critical that the Australian Government develops a sustainable population plan with stabilisation of population growth as an option. The plan needs to ensure adequate hospitals and healthcare services, education facilities, road infrastructure, sustainable transport options, water quality and quantity, utilities and other amenities that are already severely overburdened in Australian cities. There is a need for a guarantee that affordable housing will be available and priority be given to training young people and Indigenous people for employment. This paper presents evidence to support the need for the stabilisation of population growth as one of the most significant measures to control climate change as well as to improve public health equity.